Dípteros caliptrados saprófagos da Mata Atlântica e Caatinga: efeitos de variáveis ambientais e espaciais e checklist dos Sarcophagidae (Diptera: Calyptratae) da Paraíba - Alves, Ana Claudia Firmino (2018)
The Diptera are one of the largest orders of Insecta. For this study were chosen two superfamilies among the Calyptratae, represented by the families Muscidae, Fanniidae, Calliphoridae and Sarcophagidae. These dipterans stand out due to their potential to carry etiological agents of various animal and human diseases, and are importants in the estimation of IPM in Forensic Entomology science, and in the identification of the degree of human interference in natural environments. The objective of this study was to evaluate the influence of spatial and environmental variables on Diptera taxocenosis throughout the state of Paraíba, as well as to contribute to the knowledge of Sarcophagidae in the Brazilian Northeast. The objective of this study was to evaluate the influence of spatial and environmental variables on Diptera taxocenosis throughout the state of Paraíba, as well as to contribute to the knowledge of Sarcophagidae in the Brazilian Northeast. For this, in the rainy season, eight areas within the Atlantic Forest and Caatinga domains were sampled. They used traps made with pets baited with human feces, banana, sardines and bovine viscera. The traps were distributed in ten sets of four traps, spaced 100 meters in each area. In order to evaluate the relative importance of spacial scales was used Additive partitioning of diversity and the similarity of the areas by using Jaccard and Morisita index. Were used three environmental variables, together geographical coordinates, to explain the variation of the species composition, calculated throught Partial Redundancy Analysis. In total 23,362 individuals belonging 56 species were collected. Was added ten new occurrence records at the Paraíba and three at the Northeast. The results showed that the taxocenosis of dipterans in the Paraíba receives a little influence of environmental variables and, practically, none of the spatial variables. Furthermore, the variation of its diversity did not increase according to spatial scale size, probably due to the high dispersion capacity inherent in the group. For the purpose of to contribute to a better knowledge of the Sarcophagidae of the Northeast, the specimens belonging to the collection of the Entomological Collection of the Department of Systematics and Ecology (DSEC) of the Federal University of Paraíba were reviewed and tagged, resulting in a checklist of the Sarcophagidae from Paraíba. The collection currently has 2,535 sarcophagidae (1,680 females and 855 males) from 31 species distributed in 14 genera, all belonging to the subfamily Sarcophaginae, from 15 municipalities. This checklist of species contributes significantly to the knowledge of Brazilian and Neotropical Sarcophagidae.